Molecular Pharmacology and Novel Potential Therapeutic Applications of Fingolimod - Pournajaf, Safura; Dargahi, Leila; Javan, Mohammad; Pourgholami, Mohammad Hossein (Frontiers in Pharmacology, 2022)
Fingolimod is a well-tolerated highly effective disease-modifying therapy successfully utilized in the management of multiple sclerosis. The active metabolite, fingolimod-phosphate acts on sphingosine-1-phosphate receptors (S1PRs) to bring about an array of pharmacological effects. While being initially recognized as a novel agent that can profoundly reduce T-cell numbers in circulation and the CNS, thereby suppressing inflammation and MS, there is now rapidly increasing knowledge on its previously unrecognized molecular and potential therapeutic effects in diverse pathological conditions. In addition to exerting inhibitory effects on sphingolipid pathway enzymes, fingolimod also inhibits histone deacetylases, transient receptor potential cation channel subfamily M member 7 (TRMP7), cytosolic phospholipase A2α (cPLA2α), lysophosphatidic acid (LPA) and activates protein phosphatase 2A (PP2A). Furthermore, fingolimod induces apoptosis, autophagy, cell cycle arrest, epigenetic regulations, macrophages M1/M2 shift and also enhances BDNF expression. According to recent evidence, fingolimod modulates a range of other molecular pathways deeply rooted in disease initiation or progression. Experimental reports have firmly associated the drug with potentially valuable therapeutic effects in immunomodulatory diseases, CNS injuries and diseases including Alzheimer’s disease (AD), Parkinson’s disease (PD) epilepsy and even cancer. Attractive pharmacological effects, relative safety, favorable pharmacokinetics and positive experimental data have collectively led to its testing in clinical trials. Based on the recent reports, fingolimod may soon find its way as an adjunct therapy in various disparate pathological conditions. This review summarizes the up-to-date knowledge about molecular pharmacology and potential therapeutic uses of fingolimod.